Advances in Spin Catalysts for Oxygen Evolution and Reduction Reactions (Small 5/2023). Issue 5 (1st February 2023) - Bai, Haoyun; Feng, Jinxian; Liu, Di; Zhou, Pengfei; Wu, Rucheng; Kwok, Chi Tat; Ip, Weng Fai; Feng, Wenlin; Sui, Xulei; Liu, Hongchao; Pan, Hui
Abstract : Oxygen Evolution and Reduction Reactions The spin effects in oxygen evolution/reduction reaction, and advances in design, characterization and mechanisms of spin catalyst are highlighted in article number 2205638 by Hongchao Liu, Hui Pan, and co‐workers. The factors that affect spin are also discussed in detail. Some general rules are obtained, and perspectives on the study of spin catalysts are given.